Implementasi Nyanyian Tradisional sebagai Media Pendidikan Etika Sosial Masyarakat Letwurung di Kepulauan Babar Maluku Barat Daya - Peter Boris Salenussa (Jurnal Ilmiah Wahana Pendidikan, 2020)
This study aims to determine whether the traditional singing of the Letwurung community can contribute to social ethics education. This research is more directed at how to find the basis of traditional singing as a normative tool in the social ethics of the Letwurung people and how the relevance of the traditional songs of the Letwurung people known as Babar songs can be used in the social life of the Letwurung community today. The research used in this paper is a qualitative research with an ethnographic approach to explain the phenomenon of traditional singing in the Letwurung community. The results of this study indicate that it turns out that in the life of the people in Letwurung, traditional songs (Babar songs) greatly contribute in developing the social ethics education of the people. This concludes that the traditional song of the Letwurung people who also bears a resemblance to the culture of Central Maluku Kapata, which is singing halfway, but differs on the meaning side where Kapata is interpreted as a strict statement that has a dominant effect pointing upward (vertically) between humans and the Its creator, while the traditional singing of the Letwurung people has a more dominant horizontal effect, so it can be said the social dimension is more pronounced. Based on this, through this traditional singing, the social ethics education of the Letwurung community greatly contributes to efforts to uphold the value of fellowship and the potential for inheriting strong values ​​in society.